Legal politics of Indonesian migrant workers (case study of the protection of female workers) - Moulinda Ramdhani; Tirtawening Tirtawening (The International Journal of Politics and Sociology Research, 2023)
It is fascinating to study the legal politics of the protection of Indonesian Migrant Workers (PMI), particularly Female Migrant Workers. It should be able to provide legal protection via Law No. 18 of 2017 concerning the Preservation of Indonesian Migan Employees and other regulations. However, this is not the case; according to a number of comparable studies, the regulation is insufficient to provide legal protection for female migrant laborers abroad. Because it does not contain a single provision that regulates the protection of the law. According to Legal Feminist Theory (LFT), this regulation is still general and has not sided with women based on its content. In the future, there must be a legal regulation that truly prioritizes historically and spiritually more vulnerable female migrant laborers whose fundamental worker and human rights have frequently been violated. The purpose of this paper is to provide the government with constructive criticism and recommendations on how to regulate the law against female migrant laborers in the future.%MCEPASTEBIN%